Church in the present tense : a candid look at what's emerging - McKnight, Scot. (Grand Rapids, Mich. : Brazos Press, 2011)
Four authors discuss important cultural, theological, philosophical, and biblical underpinnings and implications of the emerging church movement. Their sympathetic yet critical assessment helps readers better understand the roots of the movement and the impact that it has had and is having on wider traditions. --from publisher description.
DVD contents: Conversations and resources: introduction to the the emerging church -- Interviews. Jason Clark -- Archbishop Rowan Williams -- Brian McLaren -- Jonny Baker -- Kester Brewin -- Peter Rollins -- Archbishop Rowan Williams (Part 2) -- Alternative Worship. Coca Cola liturgy -- Labyrinth -- Grace Church montage -- Soul space.
Accompanying DVD includes interviews with several individuals about the emerging church movement.
Includes bibliographical references (p. 147-150) and index.
System requirements for accompanying videodisc: DVD player.
Keywords: Emerging church movement; Christianity -- 21st century; Church renewal; Postmodernism -- Religious aspects -- Christianity